In vitro anthelmintic activity of the crude hydroalcoholic extract of Piper cubeba fruits and isolated natural products against gastrointestinal nematodes in sheep - Paula Carlis, Matheus Souza de [UNESP]; Feboli, Aline [UNESP]; Laurentiz, Antonio Carlos de [UNESP]; Filardi, Rosemeire da Silva [UNESP]; Prizantelli de Oliveira, Anna Helena; Andrade e Silva, Marcio Luis; Anjos, Luciano Alves dos [UNESP]; Magalhaes, Lizandra Guidi; Laurentiz, Rosangela da Silva de [UNESP] (Elsevier B.V., 2019)
This study describes the in vitro anthelmintic activity of a hydroalcoholic extract from the fruit of Piper cubeba and its major isolated components against the eggs and larvae of gastrointestinal nematodes obtained from naturally-infected ovines. In vitro anthelmintic activity was evaluated using the egg hatch test (EHT), larval development test (LDT) and L3 migration inhibition test (LMT). The extract showed ovicidal and larvicidal activity, with an EC50 of 200 mu g/mL and 83.00 mu g/mL in the EHT and LDT, respectively. The extract inhibited 100% of larval migration at the lowest tested concentration (95 mu g/mL). The crude extract was purified using successive silica gel chromatographic columns, which revealed the lignans hinokinin, cubebin and dihydrocubebin as the major compounds that were present, which were then used in in vitro tests. Cubebin, dihydrocubebin and hinokinin showed higher activity than the crude extract, with an EC50 for ovicidal activity of 150.00 mu g/mL, 186.70 mu g/mL and 68.38 mu g/mL, respectively. In the LDT, cubebin presented an EC50 of 14.89 mu g/mL and dihydrocubebin of 30.75 mu g/mL. Hinokinin inhibited 100% the larval development at all concentrations evaluated. In the LMT, dihydrocubebin inhibited 100% the larval migration in all concentrations evaluated while cubebin and hinokinin showed EC50 values of 0.89 mu g/mL and 0.34 mu g/mL, respectively. P. cubeba extract is rich in several classes of active compounds, but here we demonstrate that the described anthelmintic activity may be related to the presence of these lignans, which are present in larger concentrations than other components of the extract. Our results demonstrate for first time the anthelmintic activity against gastrointestinal nematodes in sheep for this class of special metabolites that are present in P. cubeba fruit. However, future detailed studies are needed to evaluate the effectiveness of P. cubeba fruits extract and active lignans in in vivo tests.
Keywords: Cubebin; Hinokinin; Dihydrocubebin; Larval migration test; Egg hatch test; Larval development test